PP-016 Timing referral of patients with intestinal failure – accumulation of preoperative comorbidities adversely affects outcome of subsequent intestinal transplantation. (23rd September 2015) - Wiles, A; Nishida, S; Tzakis, A; Sivaprakasam, R; Watson, C; Butler, A; Jamieson, N; Duncan, S; Woodward, J; Gabe, S; Middleton, S J
Abstract : Introduction: The decision to refer patients for intestinal transplantation is often taken at a stage when patients are physically and psychologically weak due to an accumulation of multiple comorbidities which may impair their post operative survival. To assist with the assessment of these patients we have developed a scoring system which can be used to prospectively follow patients and avoid untimely referral. We have developed a preliminary preoperative scoring system for transplantation of the small intestine either alone or as a composite graft. Methods: The score combines putative risk factors for survival. Factors included were loss of venous access, impairment of organs or systems not corrected by transplantation. Each factor was scored 0–3. A score of 3 indicated comorbidity approaching a contraindication for transplantation, that which might lead to but was not currently an adverse risk factor scored 1 and that presenting a definite but moderate increase in risk scored 2. The preoperative scores for 20 patients, who had either been followed up post operatively for at least 10 years or died, was compared to their survival. Results: Post operative survival and CaMi score inversely correlated when analysed using (Spearman's test) r = -0.82 p = 0.0001. A score of <3 associated with survival ≥3 years (12/12 patients) and above 3 with survival of <6 months (4/4). Patient Km survival curves for patients grouped according to CaMi score became significantly different from group 0 at group 3. Using this as a threshold score patients were grouped as either >2 or below 3 and had significantly different survival rates, (logrank, p= 0.0001), Km median survival hazard ratio (HR) 6, rate of death Km HR of 5. Receiver – operator characteristics indicate a high degree of accuracy for prediction of death at 3 years, area under curve (C statistic): 0.98; 5 years: C statistic 0.82; 10 years: C statistic 0.65. Conclusion: In this initial validation the preoperative CaMi score seems to predict postoperative survival and will now be applied to a larger population of patients for further validation and may be of use to physicians caring for patients with established intestinal failure as an additional guide to the timing of referral for transplantation.